Marker assisted selection of low phytic acid trait in maize (Zea mays L.). Issue 1 (13th March 2014) - Sureshkumar, S.; Tamilkumar, P.; Senthil, N.; Nagarajan, P.; Thangavelu, A. U.; Raveendran, M.; Vellaikumar, S.; Ganesan, K. N.; Balagopal, R.; Vijayalakshmi, G.; Shobana, V.
<x xml:space="preserve">Abstract</x> Maize is the third important major food crop. Breeding for low phytate maize genotypes is an effective strategy for decreasing the content of kernel phytic acid (a chelator of cations such as Ca2+ and Fe3+) and thereby increasing the bioavailability of nutritive minerals in human diet and animal feed. Previous studies have established that a mutant plant with a lpa2‐2 allele accumulates less phytic acid in seeds. Therefore, the marker assisted backcross breeding (MABB), which involves introgression of lpa2‐2 recessive allele (which confer low phytate trait) from a lpa2‐2 mutant line into a well‐adapted line using backcrosses and selection of lines possessing lpa2‐2 allele in each backcross population using molecular markers, is an effective strategy for developing low phytate maize. So far, no studies have developed any lpa2‐2 allele specific molecular markers for this purpose. Here, using backcross and selfed progenies, obtained by crossing low phytate mutant line 'EC 659418' (i.e. donor of lpa2‐2 allele) into agronomically superior line 'UMI395', we have validated that a SSR marker 'umc2230', located 0.4 cM downstream of lpa2‐2, cosegregate, in a Mendelian fashion, with low phytic acid trait. Therefore umc2230 can be dependably used in MABB for the development of low phytate maize.